Clinical impact of crizotinib on central nervous system progression in ALK-positive non-small lung cancer. (July 2016) - Yoshida, Tatsuya; Oya, Yuko; Tanaka, Kosuke; Shimizu, Junichi; Horio, Yoshitsugu; Kuroda, Hiroaki; Sakao, Yukinori; Hida, Toyoaki; Yatabe, Yasushi
Highlights: We evaluated the clinical impact of crizotinib on central nervous system progression in ALK-positive NSCLC. The common progression site in ALK-positive patients treated with crizotinib was the CNS. BM treatment was significantly associated with both PFS in crizotinib-treated patients and the occurrence of CNS progression. Abstract: Background: The central nervous system (CNS) is a preferential progression site related to poor penetration of crizotinib into the CNS in anaplastic lymphoma kinase (ALK)-positive non-small cell lung cancer (NSCLC) patients treated with crizotinib. We evaluated the clinical impact of crizotinib on central nervous system progression in ALK-positive NSCLC. Methods: Between January 2006 and September 2015, 59 ALK-positive NSCLC patients treated with crizotinib as the initial ALK inhibitor were retrospectively evaluated for baseline characteristics, initial response to crizotinib, brain metastasis (BM) status at baseline, and progression patterns. Results: Among 59 patients, 48 (81%) received crizotinib as first-line or second-line treatment for advanced or recurrent disease. Out of the 26 (44%) patients who had BM, 13 had untreated BM, and 13 had previously undergone intracranial radiotherapy or surgery. The overall response rate for crizotinib was 66%, with a median progression-free survival (PFS) of 9.7 months. Disease progression assessed by response evaluation criteria in solid tumors-progressive disease (RECIST-PD) occurred in 48 patients. The CNS was the common initial progression site in 24 patients, which included isolated CNS progression in 18 patients. There was a significantly shorter median PFS in the BM versus the non-BM patients before crizotinib treatment (median PFS: 6.7 months vs. 10.2 months, P = 0.0347). Multivariate analysis revealed that poor performance status (PS) (≥2) or untreated BM were associated with the PFS duration (poor PS: hazard ratio (HR) 3.322, 95% CI 1.402–7.353, P = 0.0078; untreated BM: HR 2.314, 95% CI 1.153–4.400, P = 0.0196). In addition, the time to the occurrence of CNS progression from the start of crizotinib was significantly shorter in the BM versus non-BM patients (11.1 vs. 22.1 months, P = 0.0255). Conclusion: The common progression site in ALK-positive patients treated with crizotinib was the CNS. BM status was significantly associated with both PFS in crizotinib-treated patients and the occurrence of CNS progression.